Nutritional Assessment of the Adolescents in the Northern State of Sudan - Khair Ahmed, Nur Mohammed; Onsa, Zeinab Osman (Pakistan Journal of Nutrition, 2014)
An investigation of the adolescents nutritional status in the Northern State was carried in urban and rural areas. 515 household chosen, populated by 1929 subjects. Adolescents aged (10